Characteristic stable structure of the myosin rod in dark muscle of yellowtail kingfish (Seriola aureovittata). (1st November 2022) - Liu, Yu; Wang, Zheming; Huang, Yizhen; Konno, Kunihiko; Tong, Tianjian; Yu, Chenxu; Zhu, Beiwei; Dong, Xiuping
Summary: The dark muscle of yellowtail kingfish is regularly consumed as fresh sashimi alongside with the ordinary muscle. Thus, in this study, three types of ATPase activities, chymotryptic digestion patterns as well as thermal unfolding of various myosin domains were determined to reveal the denaturation characterisation of myosin in dark muscle and compare it with normal muscle. The thermal inactivation rate of dark muscle myosin Ca 2+ ‐ATPase at 30°C (7.3 × 10 −4, sec −1 ) was significantly ( P  < 0.05) greater than that of ordinary muscle (5.9 × 10 −4, sec −1 ), while dark muscle myosin became more stable than ordinary muscle one once bound with F‐actin. On the other hand, the rod region especially light meromyosin region of the dark muscle myosin was much more stable than ordinary myosin. These results characterised that myosin in the dark muscle of yellowtail kingfish is constituted with less stable head and more stable rod regions than those in the ordinary muscle.